Utilization of Vermiwash for the Production of Liquid Biofertilizers and Its Effect on Viability of Inoculant Bacteria and Green Bean Germination - Arfarita, Novi; Lestari, Mahayu Woro; Prayogo, Cahyo (AGRIVITA Journal of Agricultural Science, 2020)
Contribution of biofertilizer in Indonesia as an alternative material for improving soil fertility and crop production is still limited. This may due to several major obstacles on its utilization and effectiveness regarding to it quality in term of its microbial viability of inoculants on formulations. This study aims to determine the effect of liquid biofertilizer formulations made from vermiwash carrier material on indigenous bacterial viability and its testing on germination of green beans ‘Vima-1’. The study included: (1) optimization of pH for the growth of inoculants bacterial consortium in vermiwash formulations with various additives, (2) viability tests and (3) pathogenicity tests of biological fertilizers on green bean sprouts (vegetative phase). The results showed that the best pH for the growth of the consortium of three bacterial isolates was at 5.5. Liquid formulation with a carrier material in the form of vermiwash plus 1% PEG (VP3 treatment) supported the highest viability of the bacterial consortium during 8 weeks incubation. All treatments did not inhibit the growth of green bean sprouts and symptom of pathogenicity was absent in all treated plants. From all treatments, the tallest green bean sprout was detected at VP3 treatment.